The missing upper Carboniferous in the Cimmerian continent: A critical review - Wang, Xiang-dong; Hu, Ke-Yi; Shi, Yu-Kun; Chen, Ji-Tao; Yang, Sun-Rong; Ye, Xun-Yan; Li, Xiao-Ming; Song, Ying-Fan; Chen, Bo; Chang, Xiao-Lin; Yao, Le; Zhang, Yi-Chun; et al. (Earth-science reviews, 2021)
The Cimmerian continent is composed of a series of blocks that were attached to the northern margin of Gondwana during the Carboniferous-Permian time, and as a consequence therefore, developed glacial sediments during the Late Paleozoic Ice Age (LPIA). These blocks rifted from Gondwana in the Early Permian, and then drifted towards the tropical area, and as a result their deposits are characterized by the mixture of warm and cool water sediments. With these previously acknowledged diagnostic features, the recognized Cimmerian blocks include Shan-Thai, Tengchong, Baoshan, Lhasa, southern Qiangtang, southern Afghanistan, and southern Iran. Carboniferous and Permian sediments and faunas in these blocks are reviewed in detail here, and disclose the most significant character of Cimmerian blocks, that is the absence of upper Carboniferous sediments, which makes them more similar to Australia and India/Pakistan, and significantly different from South China and other Tethyan regions. By the same token, central Iran, central Afghanistan, and central Pamir should be excluded from the Cimmerian blocks for distinct geological histories. The lower Carboniferous sediments present in all the Cimmerian blocks are composed of Tournaisian and Visean stages, characterized by chert nodules or lenses and oolites. Tournaisian brachiopod Syringothyris, rugose coral Cyathaxonia fauna and Siphonophyllia, and Visean bryozoan Fenestella are typical components, but overall the early Carboniferous fauna shows a Eurasian affinity. Lower Permian deposits are glacial-marine siliciclastic sequence containing cool/cold-water bivalves, small solitary non-dissepimented corals, characteristic brachiopods, low diversified but highly abundant fusulinds Pseudofusulina and Eoparafusulina, which belong to the Peri-Gondwanan fauna. The basaltic magmatism event that took place in the Cimmerian blocks was mainly in the Artinskian, which was most likely related to the initial rifting of the Cimmerian from the northern margin of Gondwana. Upper Lower Permian to Middle Permian include siliciclastics and carbonates in which cold- and warm-water mixed fauna and warm-water genera developed indicating the northward drifting of Cimmerian blocks. The marine fossils in this period are named as the Cimmerian fauna to include such characteristic taxa as the rugose coral Thomasiphyllum, fusulinids Monodiexodina and Eopolydiexodina, as well as some tropically-distributed Tethyan elements. The Upper Permian are mainly dolomitic limestones which contain the typical Cimmerian foraminifera Shanita and Hemigordius in addition to other Tethyan taxa such as the compound coral Waagenophyllum.